Small-angle X-ray and nuclear-magnetic resonance study of siloxane-PMMA hybrids prepared by the sol-gel process - Sarmento, VHV; Dahmouche, K.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Craievich, A. F. (Blackwell Munksgaard, 2003)
Transparent siloxane-polymethylmethacrylate (PMMA) hybrids were synthesized by the sol-gel process through hydrolysis of methacryloxyproyltrimethoxysilane (TMSM), tetramethoxysilane (TMOS) and polymerization of methylmethacrylate (MMA) using benzol peroxide (BPO) as catalyst. These composites have a good chemical stability due to the presence of covalent bonds between the inorganic (siloxane) and organic (PMMA) phases. The effects of siloxane content, pH of the initial sol and BPO content on the structure of the dried gels were analyzed by small-angle X-ray scattering (SAXS). SAXS results revealed the presence of an interference (or correlation) peak at medium q-range for all compositions, suggesting that siloxane groups located at the ends of PMMA chains form isolated clusters that are spatially correlated. The average intercluster distance - estimated from the q-value corresponding to the maximum in SAXS spectra - decreases for samples prepared with increasing amount of TMSM-TMOS. This effect was assigned to the expected increase in the number density of siloxane groups for progressively higher siloxane content. The increase of BPO content promotes a more efficient polymerization of MMA monomers but has no noticeable effect on the average intercluster distance. High pH favors polycondensation reactions between silicon species of both TMOS and TMSM silicon alcoxides, leading to a structure in which all siloxane clusters are bonded to PMMA chains. This effect was confirmed by Si-29 nuclear-magnetic resonance (NMR) measurements.
Keywords: PMMA; hybrid; sol gel; SAXS